Factors associated with zero vegetable and fruit consumption among Tanzanian children - Beminate Lemma Seifu; Bezawit Melak Fente; Zufan Alamrie Asmare; Angwach Abrham Asnake; Meklit Melaku Bezie; Hiwot Atlaye Asebe; Mamaru Melkam; Yohannes Mekuria Negussie (BMC, 2024)
Abstract Background Proper nutrition during early childhood is essential for healthy growth and development, yet many children, particularly in low and middle-income countries, fail to meet recommended intake levels of fruits and vegetables. This study aims to assess the factors associated with zero vegetable and fruit (ZVF) consumption among children aged 6-23 months in Tanzania, using data from the 2022 Tanzania Demographic and Health Survey (DHS). Methods A weighted sample of 4582 children aged between 6 and 23 months were included in the study. Data cleaning, coding, and analysis were performed using STATA version 17 software. To address the hierarchical nature of the DHS data and the binary outcome variable, a multilevel mixed-effect binary logistic regression model was used. The deviance value served as a guide for determining the best-fitting model. In the subsequent multivariable multilevel binary logistic regression analysis, adjusted odds ratios were computed alongside their respective 95% confidence intervals to evaluate the strength of association, with statistical significance set at a p-value below 0.05. Result The overall proportion of ZVF consumption among children aged 6-23 months in Tanzania was 48.34% (95% CI: 46.87, 49.81). Current breastfeeding status, maternal educational status, household wealth index, sex of the household head, and community poverty level were associated with higher odds of ZVF consumption. Meanwhile, child age, maternal employment status, father's educational status, and media exposure were associated with lower odds of ZVF consumption. Conclusion Child age, current breastfeeding status, maternal educational status, maternal employment status, father's educational status, household wealth index, sex of household, media exposure, and community poverty level were significantly associated with ZVF consumption. Efforts should focus on educating mothers about the early introduction of fruits and vegetables in children's diets, alongside supporting breastfeeding. Tailored economic empowerment initiatives are needed in impoverished communities to improve access to nutritious foods.